Blood Pressure after Endovascular Therapy for Ischemic Stroke (BEST): A Multicenter Prospective Cohort Study. Issue 12 (December 2019) - Mistry, Eva A.; Sucharew, Heidi; Mistry, Akshitkumar M.; Mehta, Tapan; Arora, Niraj; Starosciak, Amy K.; De Los Rios La Rosa, Felipe; Siegler, James Ernest; Barnhill, Natasha R.; Patel, Kishan; Assad, Salman; Tarboosh, Amjad; et al.
Abstract : Background and Purpose—: To identify the specific post-endovascular stroke therapy (EVT) peak systolic blood pressure (SBP) threshold that best discriminates good from bad functional outcomes (a priori hypothesized to be 160 mm Hg), we conducted a prospective, multicenter, cohort study with a prespecified analysis plan. Methods—: Consecutive adult patients treated with EVT for an anterior ischemic stroke were enrolled from November 2017 to July 2018 at 12 comprehensive stroke centers accross the United States. All SBP values within 24 hours post-EVT were recorded. Using Youden index, the threshold of peak SBP that best discriminated primary outcome of dichotomized 90-day modified Rankin Scale score (0–2 versus 3–6) was identified. Association of this SBP threshold with the outcomes was quantified using multiple logistic regression. Results—: Among 485 enrolled patients (median age, 69 [interquartile range, 57–79] years; 51% females), a peak SBP of 158 mm Hg was associated with the largest difference in the dichotomous modified Rankin Scale score (absolute risk reduction of 19%). Having a peak SBP >158 mm Hg resulted in an increased likelihood of modified Rankin Scale score 3 to 6 (odds ratio, 2.24 [1.52–3.29], P <0.01; adjusted odds ratio, 1.29 [0.81–2.06], P =0.28, after adjustment for prespecified variables). Conclusions—: A peak post-EVT SBP of 158 mm Hg was prospectively identified to best discriminate good from bad functional outcome. Those with a peak SBP >158 had an increased likelihood of having a bad outcome in unadjusted, but not in adjusted analysis. The observed effect size was similar to prior studies. This finding should undergo further testing in a future randomized trial of goal-targeted post-EVT antihypertensive treatment. Abstract : Supplemental Digital Content is available in the text.